The determinants of the commercial banks’ credit potential in a mixed money system - E. SCHNEIDER (PSL Quarterly Review, 2014)
The article takes up the question of the creation of bank money and the nature and statistical measurement of the various factors determining the volume of deposits, with a view to deducing the level of “credit potential” of the commercial banks. The author defines the respective role of the Central Bank, the commercial banks and the non-banks in determining variations in banking deposits and recalls the efforts made so far to measure these factors, the statistical difficulties involved and the methodological assumptions. The author then reaffirms the general validity of the Keynesian assumption that “in all cases the Central Bank is and remains the controller of the credit system and of the volume of credit. It is exclusively within the Central Bank’s power to determine the extent to which it will give the banks surplus cash or take it away from them”.